Literature review of international empirical research on transfer of vocational education and training. (22nd July 2022) - Toepper, Miriam; Zlatkin‐Troitschanskaia, Olga; Kühling‐Thees, Carla
Abstract: Although the practice of transferring vocational education and training (VET) structures internationally has a long tradition, there is still a lack of systematic research in this field. The various theoretical models and empirical approaches applied to analyse the transfer of the internationally very heterogeneous VET systems result in a strong fragmentation of the research landscape. Hence, consolidation and synthesizing efforts in international VET transfer research are required. This study focuses on the empirical research on VET transfer, analysing the impact and the evidential quality of the study results, and their significance. In this systematic literature review, a total of 231 relevant studies were found and of these, 26 studies were selected for full‐text analysis based on predefined criteria. These empirical studies were analysed in a two‐step procedure. First, the studies were classified into predefined superordinate categories (e.g., year, research objective, method, sample, participating countries, central result). Second, they were analysed in more depth following an integrative framework based on a research pyramid model and a model for assessing the quality of qualitative research. This critical twofold analysis of the current relevant literature indicates that there is extensive research on international VET transfer. So far, this field of research is characterized by case studies with predominantly qualitative designs and analysis methods. More methodological diversity, which includes longitudinal studies and comparative analyses, is important to this field to provide more well‐founded research outcomes in the future. These, in turn, could provide practical and political actors with an evidence‐based foundation for their decision‐making. By identifying the specific strengths and shortcomings of the empirical research on VET transfer, we reveal central desiderata and derive recommendations on how to strengthen future research and evidence‐based VET practice.